Adverse Effects of Climate Change on Agriculture: An Evaluation of Fruit and Honey Bee Farming - Sayğı , Hülya (Asian Journal of Agriculture and Rural Development, 2020)
Agriculture is one of our most basic activities that are done depending on nature with scarce resources and directly affects our life and nature. This activity, which we have met our needs from past to present, is under threat due to climate change and will not be able to produce the expected benefits in the future if measures are not taken immediately. In this study, the negative effects of climate change on agriculture are discussed under the sub-heading fruit production and bees that have an active role in fruit production. In this study, secondary data sources related to the subject (academic publications, explanations by authorized institutions and organizations, and future projections created by them) were used. The findings obtained in the study reached that if the necessary steps regarding climate change are not taken immediately, the presence of bees will decrease. As a result, fruit production will be negatively affected because pollination, which is the main factor in fruit production.